1991
DOI: 10.3109/10428199109068054
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor Production in B Cell Chronic Lymphocytic Leukemia

Abstract: Tumor necrosis factor (TNF) has been suggested to act as an autocrine growth factor in chronic B cell malignancies. We have attempted to assess the role of TNFα in relation to the stage of chronic lymphocytic leukemia (CLL) by examining TNFα cytotoxic activity of media conditioned by stimulated and unstimulated peripheral blood mononuclear cells (PBMC) and by separated unstimulated malignant B cells from Rai stage 0 and IV patients. The response of PBMC from stage IV to stimulation with phytohemagglutinin, or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Higher TNFα levels are associated with more aggressive disease [ 12 , 13 ], although CLL cells with aggressive clinical behavior make less TNFα than cells from patients with indolent disease. [ 13 , 18 , 22 ]. TNFα in the plasma of an additional 43 patients was found to correlate inversely with IgG level at the same time-point.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher TNFα levels are associated with more aggressive disease [ 12 , 13 ], although CLL cells with aggressive clinical behavior make less TNFα than cells from patients with indolent disease. [ 13 , 18 , 22 ]. TNFα in the plasma of an additional 43 patients was found to correlate inversely with IgG level at the same time-point.…”
Section: Resultsmentioning
confidence: 99%
“…3 B,C) were not obviously different in terms of these factors. Although it has been reported that lack of spontaneous production of TNFα by CLL cells is associated with clinically aggressive behavior [ 13 , 18 , 22 ], there are no obvious clinical characteristics that distinguish group 1 and group 2 patients ( Fig. 5 , Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Among different tumor-cell products, certain cytokines are known for their ability to induce procoagulant activity on endothelial cells or macrophages (72). Evidence for production of cytokines with these properties has been demonstrated in benign and malignant (83)(84)(85)(86)(87) lymphoid disorders; in short term cultures of acute (72); and in cultured melanoma (88,89), squamous carcinoma (90), and fibrosarcoma cell lines (73).…”
Section: B Mechanisms Of Extrgvascular Activation Of Coagulation Patmentioning
confidence: 99%
“…The production of IL-1 and TNF in cancer patients has been reported to be defective in some cancers [11,15,31] as well as comparable or increased in others [1,13,28,29]. According to our results (Table 1), unstimulated monocytes from patients of both the groups showed a slightly higher level of IL-1 activity than normal donors which was not found to be significant.…”
Section: Inhibition Of Monocyte Cytotoxicity By Monoclonal Antibody Tmentioning
confidence: 40%